2021
DOI: 10.1016/j.crfs.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of flaxseed (Linum usitatissimum) oil with carotenoids of sea buckthorn pomace via ultrasound-assisted extraction technique

Abstract: Currently, flaxseed oil is used as an important functional food constituent owing to its large content of omega-3 fatty acids. However, flaxseed oil does not contain carotenoids that could enhance the oxidative stability of the oil. In this study, carotenoids extracted from sea buckthorn pomace were used to enrich cold-pressed flaxseed oil via an ultrasound-assisted extraction technique (UAE). The process parameters were optimized through Box-Behnken design to maximize the carotenoid content in the flaxseed oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The results showed a significant difference at the level of probability (P < 0.05) between time (0) and the other times (5,10,15), and also there are significant differences at the probability level (P < 0.05) among times 5, 10, 15. This is close to study of [24], conducted on the extraction of oil from tobacco by ultrasound which cased decreasing in iodine number, while disagree with other study [28], which indicated that there was a slight increase in the value of iodine in flax oil extracted with ultrasound.…”
Section: Iodine Numbersupporting
confidence: 60%
“…The results showed a significant difference at the level of probability (P < 0.05) between time (0) and the other times (5,10,15), and also there are significant differences at the probability level (P < 0.05) among times 5, 10, 15. This is close to study of [24], conducted on the extraction of oil from tobacco by ultrasound which cased decreasing in iodine number, while disagree with other study [28], which indicated that there was a slight increase in the value of iodine in flax oil extracted with ultrasound.…”
Section: Iodine Numbersupporting
confidence: 60%
“…The following parameters were considered optimal process conditions: 75.5 min, 80.8%, frequency 20 kHz and dosage 19.9. The procedure resulted in 14.2 mg/L of carotenoids recovered from the supernatant [36]. Stupar et al (2021) in their study presented an ultrasound-assisted extraction of carotenoids from pumpkin using natural deep euthetic solvents.…”
Section: Ultrasound-assisted Extraction (Uae)mentioning
confidence: 99%
“…UAE has been used to extract carotenoids from different fruits and vegetables by-products such as acerola, guava, genipap and umbu seeds and peels ( 72 ), carrot pomace ( 73 , 81 ), cantaloupe peel ( 82 ), mandarin peel ( 54 , 83 , 84 ), Gac fruit peel ( 63 ), mango peel and paste ( 85 ), peel of different varieties of orange ( 38 , 43 , 48 ), orange pomace ( 86 ), pepper leaves ( 87 ), pomegranate peel ( 55 ), pumpkin peel ( 88 , 89 ), purple passion fruit peel ( 90 ), sea buckthorn pomace ( 49 , 91 , 92 ), tomato peel and seeds ( 31 , 93 95 ), and arthropods by-product such as shrimp shell and cephalothorax ( 40 , 96 98 ). According to these studies, carotenoids can be used as a natural pigment directly in the preparation of various food products such as butter, salad dressing, beverages, ice cream, desserts, candy, bakery, edible oils, meet products, cosmetics, pharmaceutical products, also as an ingredient in feed for aquatic animals and pets.…”
Section: Extraction Of Natural Pigments With Ultrasound-assisted Extr...mentioning
confidence: 99%
“…Therefore, carotenoids can be highlighted as a promising natural colorant for application mainly in the food industry ( 97 ), also as an ingredient owning healthy components for the development of functional foods ( 92 , 98 ). Extracted carotenoids can be used in the form of enriched edible oils ( 91 ), or can be integrated into high water content food products as a spray-dried powder ( 95 ). However, the carotenoids use can be limited by some interactions with other compounds in food products.…”
Section: Extraction Of Natural Pigments With Ultrasound-assisted Extr...mentioning
confidence: 99%